Language and literacy teaching for indigenous education : a bilingual approach - Francis, Norbert (Bilingual education and bilingualism ;, 2002)
Language and Literacy Teaching for Indigenous Education: A Bilingual Approach presents a proposal for the inclusion of indigenous languages in the classroom. Based on extensive research and field work by the authors in communities in the United States and Mexico, the book explores ways in which the cultural and linguistic resources of indigenous communities can enrich the language and literacy program.